What Works to increase Financial Inclusion and Women’s Financial Autonomy? Intentional Designs showing Promise - Eckhoff, Sarah; Kibombo, Grace Majara; Natukunda, Melch Muhame; Pennotti, Christian; Vandergaag, Karen (Development in Practice, 2019)
Despite gains in financial inclusion and evidence that increased access to services improves women’s ability to realise their goals, a gender access gap to financial services of 9 percentage points prevails in lower-income countries. This stubborn reality calls for new approaches to reaching and supporting women to access financial services, including greater consideration of the gender norms and institutions that inhibit women’s full use of financial services. This article shares two experiences where CARE worked with partner banks and local non-profits to deliver financial services coupled with intentional interventions designed to address gender norms.
Keywords: Gender and diversity; Labour and livelihoods; Poverty reduction